Pengaruh perceived usefulness, perceived ease of use dan perceived enjoyment terhadap penerimaan teknologi informasi web SMB Universitas Telkom - Widaningsih, Sri; Mustikasari, Ati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Generation Z is a generation that is well versed in technology, understands networks and is familiar with applications, so it is faster and easier for them to access various information needed, both for educational purposes and for the purposes of daily life. In addition, they are also able to interact with all walks of life through social media very intensely, are accustomed to doing various activities at the same time, and are easy to change. The purpose of this study is to evaluate whether the Telkom University SMB web is classified as successful and accepted by web users using the Technology Acceptance Model (TAM) method. Collecting data in this study using a questionnaire to the community in the city of Bandung. The number of respondents was 210 people, with the sampling technique used was purposive sampling. The analytical test tools used are Descriptive Analysis and Structure Equation Model (SEM). The results of this study indicate that perceived usefulness, perceived ease of use, perception of convenience, and attitudes towards use can influence the adoption of